Comparing the Evolution of Risk Culture in Radiation Oncology, Aviation, and Nuclear Power. Issue 4 (December 2020) - Abdulla, Ahmed; Schell, Kristen R.; Schell, Michael C.
Abstract : Objectives: All organizations seek to minimize the risks that their operations pose to public safety. This task is especially significant if they deal with complex or hazardous technologies. Five decades of research in quantitative risk analysis have generated a set of risk management frameworks and practices that extend across a range of such domains. Here, we investigate the risk culture in three commercial enterprises that require exceedingly high standards of execution: radiation oncology, aviation, and nuclear power. Methods: One of the characteristics of high reliability organizations is their willingness to learn from other such organizations. We investigate the extent to which this is true by compiling a database of the major publications on risk within each of the three fields. We conduct a bibliographic coupling analysis on the combined database to identify connections among publications. This analysis reveals the strength of engagement across disciplinary boundaries and the extent of cross-adoption of best practices. Results: Our results show that radiation oncology is more insulated than the other two fields in its adoption and propagation of state-of-the-art risk management tools and frameworks that have transformed aviation and nuclear power into high reliability enterprises with actuarially low risk. Conclusions: Aviation and nuclear power have established risk cultures that cross-pollinate. In both nature and extent, we found a distinct difference in radiation oncology's engagement with the risk community, and it lags behind the other two fields in implementing best practices that might mitigate or eliminate risks to patient safety. Abstract : Supplemental digital content is available in the text.